THE EXISTENCE OF TRADITIONAL LAW REVIEWING FROM PANCASILA VALUES IN THE DEVELOPMENT OF NATIONAL LAW - Nova Yarsina (STIH Putri Maharaja, 2021)
The purpose of this study is to examine the existence of customary law in terms of Pancasila values in the development of national law and what factors influence the existence of customary law in terms of Pancasila values in the development of national law. The research method used is normative juridical. The Indonesian people have succeeded in carrying out legal reforms to the constitution. Legal reform must continue with the formation and renewal of laws replacing Dutch legacy laws. Having its own laws for the Indonesian people can reveal national identity. Legal development simply implies efforts to make improvements from unfavorable conditions to better ones. According to this understanding, development can be meaningful with renewal. Reform is an effort to reorient and reform something that will be pursued through policy. The development of national law is the process of building a legal system and its instruments. The development of national law must be able to replace all Dutch Colonial product laws replaced with their own product laws. Legal development cannot be separated from legal politics, because it is a direction in making and enforcing laws in order to achieve national goals and objectives. Law as mentioned in the Oxford English Dictionary is a collection of rules either as a result of formal legislation or custom, in which a certain state or society claims to be bound as members or as subjects. Law is a behavioral control system (ethical control). The legal form is a norm which is the product of a center of power that has the authority to create and apply the law. Law as a unidirectional control system carried out by a central organ that has power. Unidirectional control implies that control only takes place from a certain organ that is given the capacity and function for it. Unidirectional control is also automatic-mechanical that guides behavior.